Animais literários e possibilidades zoopoéticas nas narrativas condeanas - Silva, Renally Kamillah Ynnaiãnh Batista Martins Bezerra da (2025)
This paper aims to present the interspecies relationships in José Condé’s narratives through an ecological reading of the literary text. We propose a thesis of perception by introducing and developing the concept of symmetrical animality. The relationships between human and non-human animals portrayed in Condé’s work are constructed from an ethics of the living, focusing on the power of affects within the interactions that occur between species. The animalistic relationships developed in the works Terra de Caruaru (1960), Pensão Riso da Noite: Rua das Mágoas (cerveja, sanfona e amor) (1966), and Tempo, vida, solidão (1971) guide us toward recognizing non-human animals as structural elements of actantial and symbolic reference. In light of Jacques Derrida’s (2002) studies, we question the traits said to be inherent to humans, and, alongside Bruno Latour (2019), discuss the possibilities of hybridity and symmetry between beings. Supported also by readings of Maria Esther Maciel (2016, 2023), we explore José Condé’s work to determine that the relationship between humans and non-humans — starting from the human-animal binary and their interactions —occurs on a distinct level of sensitivity and promotes animalistic agencies that transcend the purely fictional, gaining space in contemporary society and becoming the primary key of analysis. We consider here the full historical complexity of human-environment interactions, suggesting a dialogue within the sphere of animal ethics and a possible reinterpretation of the nature-society duality by incorporating animalities, historical processes, evolutionary paths, and psychological indicators. Based on a sociocultural study of how animalistic relationships occur historically, we specifically selected the horse, the goat, the rat, and the dog from Condé's narrative to analyze their actantial powers, allowing us to suggest a symmetrical animality based on the zoopoetic reading of José Condé's work. Animals act as the human’s double, absorbing and being affected by the social sphere; what they reflect is the human in its singular form, often isolated from society (by choice or necessity), on the margins. The presence and significance of non-human animals in Condé’s narratives suggest a destabilization of behavioral patterns that imply a certain human superiority. The figures presented here suggest a revision of terms, attitudes, and concepts.